The ophthalmological complications of targeted agents in cancer therapy: what do we need to know as ophthalmologists?. (12th September 2012) - Ho, Wing L.; Wong, Hilda; Yau, Thomas
Abstract. Recently, there has been an increase in the use of targeted therapies for cancer treatments. Nevertheless, the ocular side‐effects of the commonly used targeted agents are generally under‐reported and not well studied in the literature. We conducted multiple searches in databases, including Medline, EMBASE, Cochrane Library and conference proceedings, using the following strings: 'name of targeted therapeutic agent (both generic and commercial names)' AND 'eye OR ocular OR vision OR ophthalmological'. Various targeted agents have been found to be associated with ocular side‐effects due to their specific targeting of activities in the eye. Imatinib commonly causes periorbital oedema, epiphora and occasionally conjunctival haemorrhage. Cetuximab causes corneal lesions, meibomian gland dysfunction, periorbital and lid dermatitis, blepharitis and conjunctivitis. Erlotinib is related to various ocular toxicities, mainly on the ocular surface, and perifosine has been reported to be associated with severe keratitis. Bevacizumab could potentially disrupt intrinsic ocular circulation and lead to the development of thromboembolic events; there are rare reported cases of optic neuritis or optic neuropathy. Other targeted agents, such as trastuzumab, sunitinib and crizotinib, also have specific ocular toxicities. In conclusion, ocular effects of targeted agents are not uncommon in cancer patients receiving targeted therapy. Ophthalmologists should have high indexes of suspicion to diagnose and treat these complications promptly.